Development of Kalam Flipbook Media for Arabic Speaking Skills of Students Grade X Madrasah Aliyah in Semarang City - Ruby Syahira; Zukhaira (Arabiyatuna: Jurnal Bahasa Arab, 2026)
This study aims to develop an interactive learning media in the form of a digital flipbook using the Heyzine Flipbook platform, designed in Canva, and to validate the product through evaluations by material experts, media experts, and stakeholders. Students’ Arabic-speaking skills are often hindered by factors such as speaking anxiety, teachers limited instructional effectiveness, and insufficient use of learning media. These challenges can be addressed by providing interactive learning media that boost student motivation, enhance understanding, and support active learning, such as flipbook-based media. The Heyzine Flipbook platform offers features such as video, audio, text, images, and quizzes, that can improve student engagement and practice. This research employed a Research and Development (R&D) approach following the ADDIE model, focusing on four stages: analysis, design, development, and evaluation. The participants were tenth-grade students from three Madrasah Aliyah in Semarang. The data were collected through interviews, questionnaires, and expert validation instruments. The expert validation results showed that the Kalam Flipbook media scored 88, placing it in the “highly feasible” category. The findings reveal that the Kalam Flipbook interactive multimedia provides an engaging learning experience and has the potential to serve as an innovative teaching tool for Arabic language learning according to expert assessment. The research limitation of this study is the absence of field testing of the developed media with students.